Personal Value, Organizational Commitment and Performance of Lecturers - Abdul Wahid Kamma (Peneliti.net, 2021)
As the vision and mission, a higher education should develop its human resources’ abilities and skills to achieve its goals. So commitment to their profession plays a role in improving lecturers’ performance and fostering their individual values ​​to accomplish the responsibility as professional educators. This study aimed to analyze the performance of lecturers based on personal values ​​and organizational commitment in Nuku University, Tidore. This research was designed to answer problems as the objectives and to test the hypothesis. The research location was in Nuku Tidore University. The population were 75 lecturers of Nuku University. The samples were taken using sampling technique to all population. Primary data were directly obtained from census or field surveys through research questionnaires to respondents in Nuku University, Tidore. Then the data were analyzed using PLS. As the results, this study indicated that well-developed personal value would establish organizational commitment and lecturers’ performance. A robust personal value was marked with stable values ​​that were carried out wholeheartedly to the pride for the university. Organizational commitment could also improve the performance of lecturers in Nuku University. Moreover, performance would develop if lecturers had a commitment to higher education continuously.